Synthesis of New Thiazole-Privileged Chalcones as Tubulin Polymerization Inhibitors with Potential Anticancer Activities - Hamada Hashem; Abdelfattah Hassan; Walid M. Abdelmagid; Ahmed G. K. Habib; Mohamed A. A. Abdel-Aal; Ali M. Elshamsy; Amr El Zawily; Ibrahim Taha Radwan; Stefan Bräse; Ahmed S. Abdel-Samea; Safwat M. Rabea (MDPI AG, 2024)
A series of novel thiazole-based chalcones were evaluated for their anticancer activity as potential tubulin polymerization inhibitors. In vitro anticancer screening for the thiazole derivatives 2a-2p exhibited broad-spectrum antitumor activity against various cancer cell lines particularly Ovar-3 and MDA-MB-468 cells with a GI50 range from 1.55 to 2.95 μΜ, respectively. Compound 2e demonstrated significant inhibition of tubulin polymerization, with an IC50 value of 7.78 μM compared to Combretastatin-A4 (CA-4), with an IC50 value of 4.93 μM. Molecular docking studies of compounds 2e, 2g, and 2h into tubulin further supported these findings, revealing that they bind effectively to the colchicine binding site, mirroring key interactions exhibited by CA-4. Computational predictions suggested favorable oral bioavailability and drug-likeness for these compounds, highlighting their potential for further development as chemotherapeutic agents.